Influence of Physico-Chemical Processing in Solid and Liquid States on Hypereutectic AlSi18(B-Sn) Alloy Structure and Properties - Aiupov, Oleksandr; Nosko, Olha A.; Aiupova, Tetyana A.; Kupchinska, Alina (Харківський національний автомобільно-дорожній університет, Україна, 2023)
ENG: The peculiarities of AK18 alloy (B-Sn) structure formation, mechanical properties, friction and wear parameters formation depending on the regimes of physical and chemical melt processing and thermocycling in the solid state have been established. Observed structural changes (the β-Si and eutectics ratio, the primary and eutectic β-Si crystals shape and size, eutectics differentiation increasing, the pseudoprimary aluminum solid solution (α-A1) dendrites appearance provide an improvement in the complex of mechanical properties and a reduction in wear friction parameters. The obtained experimental data allow to recommend a complex treatment "hydrogen treatment for 40 min + thermal cycling in the solid state at 475-485°C for 5 cycles" to improve the complex of mechanical properties and reduce the wear friction parameters.

UKR: Встановлені особливості стуктуроутворення, формування механічних властивостей, параметрі тертя і зносу сплаву АК18 (В-Sn) в залежності від режимів фізико-хімічної обробки розплаву і термоциклювання в твердому стані. Спостережувані структурні зміни (співвідношення β-Si та евтектики, форми і розміру первинних і евтектичних кристалів β-Si, підвищення диференціювання евтектики, появі дендритів псевдопервинного алюмінієвого твердого розчину (α-А1) забезпечують поліпшення комплексу механічних властивостей та зниження параметрів тертя зносу. Отримані експериментальні дані дозволяють рекомендувати комплексну обробку «воднева обробка 40 хв + термоціклювання в твердому стані при 475-485°С 5 циклів» для поліпшення комплексу механічних властивостей та зниження параметрів тертя зносу.
Вплив фізико-хімічної обробки в твердому та рідкому станах на структуру та властивості заевтектичного силуміну АК18(B-Sn)
О. Nosko: ORCID 0000-0002-5749-7578; T. Aiupova: ORCID 0000-0002-5706-4211
Keywords: hyper-eutectic AlSi alloy; microalloying; hydrogen treatment; hydrocircular treatment; thermal sycling; заевтектичний силумін; сплав AlSi; мікролегування; воднева обробка; гідро циркуляційна обробка; термоциклювання; КМТОМ; КПМ і ЗМ; TECHNOLOGY::Materials science